Measuring the Performance Characteristics of a Motorcycle - Hamberger, Adam; Daňa, Milan (Manufacturing Technology Journal, 2019)
This work deals with an experiment, whose output is the comparison of power characteristics which were measured in three ways. The first way used a commercially manufactured dynamometer. For the second measurement, a special dynamometer with our own computing system and a sensor within this project was created. The last way of measuring the performance characteristics was done without a dynamometer. The measurement works on the principle of acceleration the spinning of a flywheel. Due to this, the measuring is called an acceleration test. The basic principles are described before the experiment in order to grasp the characteristics. All explanations are based on schemes and easy mathematical and differential formulas to describe the construction of the dynamometer and the principle of its functions from the engine to the computer. The relations between published and unpublished quantities defining engine dynamics are explained here. In the end, this work points to possible and intended measuring failures which are an infamous practice at many measuring stations.
Keywords: Dynamometer; power characteristics; driving forces; torque; performance